2007
DOI: 10.1037/1064-1297.15.2.186
|View full text |Cite
|
Sign up to set email alerts
|

Delay discounting predicts postpartum relapse to cigarette smoking among pregnant women.

Abstract: Delay discounting (DD), a measure of impulsivity, describes the rate at which rewards lose value as the delay to their receipt increases. Greater discounting has been associated with cigarette smoking and various other types of drug abuse in recent research. The present study examined whether DD predicts treatment outcome among cigarette smokers. More specifically, the authors examined whether baseline discounting for hypothetical monetary rewards predicted smoking status at 24 weeks postpartum among women who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
283
4
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(324 citation statements)
references
References 66 publications
30
283
4
2
Order By: Relevance
“…Indeed, a comprehensive assessment including neurocognitive tasks indexing different aspects of impulsivity within the same sample may help to clarify which dimensions are more important to certain outcomes than others. However, the majority of studies selected for this review (n=16) measured only one neurocognitive dimension of impulsivity (Black & Rosen, 2011;Bowden-Jones et al, 2005;Brewer et al, 2008;Carpenter et al, 2006;Cox et al, 2002;Janes et al, 2010;Marissen et al, 2006;Peters et al, 2013;Stanger et al, 2012;Streeter et al, 2008;Washio et al, 2011;Waters et al, 2003;Winhusen et al, 2013;Yoon et al, 2007). In contrast, only six studies assessed two neurocognitive dimensions of impulsivity De Wilde et al, 2013;Mueller et al, 2009;Schmitz et al, 2009; and even a smaller number of studies (n=3) used a test battery indexing three different impulsivity domains Sheffer et al, 2012) (see Table 1).…”
Section: Impulsivity Constructs Measuredmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a comprehensive assessment including neurocognitive tasks indexing different aspects of impulsivity within the same sample may help to clarify which dimensions are more important to certain outcomes than others. However, the majority of studies selected for this review (n=16) measured only one neurocognitive dimension of impulsivity (Black & Rosen, 2011;Bowden-Jones et al, 2005;Brewer et al, 2008;Carpenter et al, 2006;Cox et al, 2002;Janes et al, 2010;Marissen et al, 2006;Peters et al, 2013;Stanger et al, 2012;Streeter et al, 2008;Washio et al, 2011;Waters et al, 2003;Winhusen et al, 2013;Yoon et al, 2007). In contrast, only six studies assessed two neurocognitive dimensions of impulsivity De Wilde et al, 2013;Mueller et al, 2009;Schmitz et al, 2009; and even a smaller number of studies (n=3) used a test battery indexing three different impulsivity domains Sheffer et al, 2012) (see Table 1).…”
Section: Impulsivity Constructs Measuredmentioning
confidence: 99%
“…Six of the 25 selected studies were conducted among primary cocaine users (Black & Rosen, 2011;Brewer, Worhunsky, Carroll, Rounsaville, & Potenza, 2008;Schmitz et al, 2009;Streeter et al, 2008;Washio et al, 2011), three among primary opiate users Passetti et al, 2008Passetti et al, , 2011, three among primary alcohol users Cox et al, 2002;De Wilde et al, 2013), eight among primary nicotine users Janes et al, 2010;Mueller et al, 2009;Sheffer et al, 2012;Waters et al, 2003;Yoon et al, 2007) and two among primary marijuana users (Peters, Petry, Lapaglia, Reynolds, & Carroll, 2013;Stanger et al, 2012). One study examined the relationship between impulsivity and treatment outcomes within a heterogeneous sample of drug users, consisting of cocaine, heroin and marijuana dependent subjects (Carpenter, Schreiber, Church, & McDowell, 2006).…”
Section: Study Design and Samplementioning
confidence: 99%
“…Some cross-sectional studies (e.g., Green et al 1994;Harrison et al 2002;Steinberg et al 2009;Yoon et al 2007) have demonstrated that younger individuals discount delayed rewards more steeply than older individuals, and they have the tendency to choose small immediate rewards, rather than larger delayed rewards declines with age (e.g., Olson et al 2007;Scheres et al 2006;Steinberg et al 2009; see Albert and Steinberg [2011] for a review). This is probably due to individual difference factors (such as future orientation and impulsivity), cognitive functioning (such as the ability to imagine and experience pleasure or pain in advance of future events), and the maturation of brain system during adolescence (Banich et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in rats suggest that high delay-discounting rates are associated with vulnerability to acquisition of cocaine self-administration (Perry, Larson, German, Madden & Carroll, 2005), greater nicotine seeking during nicotine extinction, and greater reinstatement of nicotine seeking by re-exposure to nicotine-associated cues (Diergaarde et al, 2008). Human studies suggest that high delay-discounting rates may predict lack of success in drugdependence treatment (Dallery & Raiff, 2007;Krishnan-Sarin et al, 2007;Yoon et al, 2007). Similarly, individuals with other psychiatric problems have also been shown to discount at high rates (Alessi & Petry, 2003;Barkley, Edwards, Laneri, Fletcher, & Metevia, 2001;Crean, de Wit, & Richards, 2000;Rounds, Beck, & Grant, 2007).…”
mentioning
confidence: 99%